2022
DOI: 10.1177/08863687221131728
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Offering Paid Leave: Benefits to the Employer, Employee, and Society

Abstract: The COVID-19 pandemic has highlighted numerous problems in the labor market in the U.S., including high and low unemployment rates, burnout of employees in many industries, and inadequate time off for caregiving and medical issues. In this manuscript, we propose that employer-sponsored paid leave is increasingly important given that the U.S. lags behind most other nations in its leave policies, and many employees, particularly those in lower-wage, part-time, or front-line occupations do not have paid leave fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…While we cannot infer that access to these benefits resulted in lessened FIS, employers should consider providing or improving these benefits before they consider new financial wellness benefits. For example, offering PTO would have a stronger effect on FIS than offering pay advances, particularly among lower-wage workers (Davison & Blackburn, 2023). Not missing a day's pay due to a child's illness will make it easier to buy food than a pay advance.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot infer that access to these benefits resulted in lessened FIS, employers should consider providing or improving these benefits before they consider new financial wellness benefits. For example, offering PTO would have a stronger effect on FIS than offering pay advances, particularly among lower-wage workers (Davison & Blackburn, 2023). Not missing a day's pay due to a child's illness will make it easier to buy food than a pay advance.…”
Section: Discussionmentioning
confidence: 99%
“…The BLS data also revealed that paid sick leave was available to 75% of all private industry workers in March 2021, ranging from 59% of workers in service jobs to 93% of workers in management, professional, and related occupations [36]. Given that access to sick leave has been shown to be an important factor in reducing the spread of infectious illnesses in workplaces [7,37,38], further research is needed to understand the impact of generous employer leave policies in promoting employee health and well-being [39] and in preventing the spread of disease in workplaces in this and future pandemics.…”
Section: Discussionmentioning
confidence: 99%